2D/3D Heterostructure for Semitransparent Perovskite Solar Cells with Engineered Bandgap Enables Efficiencies Exceeding 25% in Four‐Terminal Tandems with Silicon and CIGS. (11th March 2020) - Gharibzadeh, Saba; Hossain, Ihteaz M.; Fassl, Paul; Nejand, Bahram Abdollahi; Abzieher, Tobias; Schultes, Moritz; Ahlswede, Erik; Jackson, Philip; Powalla, Michael; Schäfer, Sören; Rienäcker, Michael; Wietler, Tobias; et al.
Abstract: Wide‐bandgap perovskite solar cells (PSCs) with optimal bandgap ( E g ) and high power conversion efficiency (PCE) are key to high‐performance perovskite‐based tandem photovoltaics. A 2D/3D perovskite heterostructure passivation is employed for double‐cation wide‐bandgap PSCs with engineered bandgap (1.65 eV ≤ E g ≤ 1.85 eV), which results in improved stabilized PCEs and a strong enhancement in open‐circuit voltages of around 45 mV compared to reference devices for all investigated bandgaps. Making use of this strategy, semitransparent PSCs with engineered bandgap are developed, which show stabilized PCEs of up to 25.7% and 25.0% in four‐terminal perovskite/c‐Si and perovskite/CIGS tandem solar cells, respectively. Moreover, comparable tandem PCEs are observed for a broad range of perovskite bandgaps. For the first time, the robustness of the four‐terminal tandem configuration with respect to variations in the perovskite bandgap for two state‐of‐the‐art bottom solar cells is experimentally validated. Abstract : A 2D/3D perovskite heterostructure passivation is employed for double‐cation wide‐bandgap PSCs with an engineered bandgap (1.65 eV ≤ E g ≤ 1.85 eV), which results in improved stabilized PCEs and open‐circuit voltages for opaque and semitransparent perovskite solar cells. Four‐terminal perovskite/c‐Si and perovskite/CIGS tandem solar cells with stabilized PCEs of up to 25.7% and 25.0%, respectively, are demonstrated.